The Debate Over Euthanasia and Human Rights - Shala, Irena; Gusha, Kilda (European Scientific Journal, ESJ, 2016)
The present article analyzes the debate on issue of euthanasia (voluntary assisted suicide) and the relevance of international human rights norms to that debate. Euthanasia is one of the most complex issues facing human rights, especially given its ethical, legal, medical and religious dimensions. These include: modern medical technology and the availability of medical measures to prolong life; In historical terms inherit challenging laws by refusing euthanasia; The phenomenon of growing older population and the large the number of people affected by AIDS; And fall the impact of religious organizations that consider life to be sacred: terminating a life, for whatever reason, not only infringes religious beliefs but may transgress divine activities beyond the reach of human beings. Justice system is an essential player in the debate. Although euthanasia is generally unlawful, there is an increasing movement towards legalization, particularly in western jurisdictions. Serious political and legal actions taken by euthanasia advocates and their lawyers have brought assisted suicide to the brink of legal assistance. In fact, legislation allowing voluntary euthanasia has been passed in a small number of jurisdictions, and domestic courts in other countries are being repeatedly asked to consider whether the interests at stake with regard to the right to die should be recognized. Die due to euthanasia in Albania is a criminal offense which is considered a violation of the right to live and punished according to the Criminal Code. But in the Code of Ethics and Deontology of the Order of Physicians, there is a provision, which allows the application of a form of interference, which can be interpreted in as passive euthanasia. And this decision remains entirely to the discretion of the physician.